Students’ Perception on English Club Extracurricular in Speaking Practices at Madrasah - Aida Yuliandasari; Wendi Kusriandi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
Speaking is one of skills which should be mastered by students in studying English. However in Indonesian school hours the chance to practice speaking is limited. One way to obtain more practices to speak outside of school hours is by joining English club extracurricular program. English club as an English extracurricular program in state Madrasah Aliyah Pembangunan Mandirancan gives chance to students to speak in more flexible condition with their peers. Thus, it is interesting to investigate the impact students perception on English club extracurricular toward students‟ speaking skill. The 26 students joined English club extracurricular as the sample. The techniques used obtaining the data were observation, questionnaire and speaking test. It is suggested that the students should joined English club extracurricular because it can improve students‟ speaking skill.